STUDENTS' PERCEPTION OF USING MEDIA PLATFORMS FOR ESL STUDENTS (A case study in SMK Darma Bahari Surabaya) - Siti Fatimah; Sulistiyani Sulistiyani (Fakultas Bahasa & Sastra Universitas Wijaya Putra, 2022)
The purpose of this study was to find out how high-school students felt about using media platforms for English learning. In this study, Students from SMK Dharma Bahari Surabaya took part. Questionnaires and semi-structured interviews were used as data collection methods in this qualitative study with a case study design. The data from the questionnaire was examined using basic statistical analysis, while the data from the interviews were analyzed using Miles and Huberman's flow model. According to the findings, students in this study use media platforms to learn and improve their English. YouTube is the most popular media platforms platform for learning English, according to them. Furthermore, they indicated that media platforms provide them with English content sources through which they may practice their English abilities, particularly listening, expand their vocabulary, and improve their pronunciation. Furthermore, because media platforms provide a wealth of English content, students can access it whenever and wherever they want. The circumstance provides a stress-free language atmosphere in which students can feel at ease and encouraged to learn English outside of the classroom.